Effect of banana cultivars and ripening stages on bioactive compounds and antioxidant capacity of fresh clear low-viscosity banana juice - Mathayo Gervas Mathias; Lilian Daniel Kaale; Oscar Kibazohi (Applied Food Research, 2024)
Food-based antioxidants reduce oxidative stress caused by metabolic processes, scavenge free radicals, promote cardiovascular health, and preventing oxidative-stress related diseases, among other health advantages. The current study aims to investigate the low-viscosity banana juices’ bioactive compounds and antioxidant capacity dependence on cultivars and ripening stages. Five banana cultivars were studied: Mbilabile, Pisang Awak (PSA), Yangambi km5 (YKM5), Ndeshi, and Mlonga. An improved mechanical extraction method involving malaxation of peeled banana pulp until low-viscosity banana juice separates from the pulp was used to extract banana juice. Considered ripening stages were stage 3; more green than yellow, 4; more yellow than green, 5; yellow with a trace of green, 6; all yellow, and 7; all yellow with brown spots. It was revealed that banana juice is rich in polyphenolic compounds 145.02–320 mg GAE/L and ascorbic acid, 0.45–1.40 g/L. In addition, the composition of total phenolic compounds (TPC) and ascorbic acid varied with banana cultivars and ripening stages. Furthermore, banana juice could reduce 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radicals by 67–93 %. The antioxidant capacity of banana juice varied with cultivars and ripening stages (p < 0.05). Correlation analysis suggested ascorbic acid influenced banana juice free radical scavenging capacity.